Study Of Lavatory Installation Methods On Ship Landing Platforms - Musa, Musa; Munazid , Ali; Suwasono , Bagiyo; Hardianto, Didik; Sutiyo, Sutiyo (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Landing Platform Dock (LPD) ships as amphibious warships with complex accommodation systems, including lavatory installations, require effective and efficient installation methods. This study was motivated by the need to compare two lavatory installation methods, namely the conventional method and the modular method, in an effort to increase productivity and reduce the amount of rework in the construction of LPD ships. The research method used is the direct observation method at the national shipyard, with data collection through installation time records, number of man hours, material costs, and number of rework events. Data were analyzed using a quantitative descriptive approach by comparing these variables in each type of lavatory. In this study, 3 types of lavatory with different dimensions and shapes were used. The modular method which requires 10-14 days to complete has proven to be significantly more efficient in terms of implementation time compared to the conventional method with results of 19-25 days according to the type of lavatory. Likewise in the number of man-hours needed, which reached 384-480 JO for the conventional method and 264-456 JO for the modular method in the three types of work. The costs incurred for this production require IDR 67,880,890 - IDR 81,377,090 for the modular method and IDR 71,682,490 - IDR 87,713,090 for the conventional method. Thus, the modular method has proven to be more effective in increasing productivity and reducing the cost of installing a better lavatory.